2019
DOI: 10.1111/ijfs.14325
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in molecular docking technology applied in food science: a review

Abstract: Molecular docking is a theoretical simulation method based on bioinformatics, which studies the interaction between molecules (such as ligands and receptors), and predicts their binding modes and affinity via a computer platform. This technology acts as a promising mean in medicinal chemistry such as structurebased rational drug design, which is accepted by researchers in the scientific community. During recent years, various fundamental studies involving biomolecular interaction in the food matrix have gradua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(80 citation statements)
references
References 138 publications
0
78
0
2
Order By: Relevance
“…The results obtained are similar to the inhibition of β‐catenin by the flavonoids studied by Hira Iftikhar [13] . In general, tumor formation occurs due to the abnormal Wnt signaling by nuclear accumulation of β‐catenin as a result of glycogen synthetase kinase‐3 (GSK‐3)β inactivation [14] . According to molecular docking results, we proposed that four anthocyanins could be more potent inhibitors of β‐catenin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained are similar to the inhibition of β‐catenin by the flavonoids studied by Hira Iftikhar [13] . In general, tumor formation occurs due to the abnormal Wnt signaling by nuclear accumulation of β‐catenin as a result of glycogen synthetase kinase‐3 (GSK‐3)β inactivation [14] . According to molecular docking results, we proposed that four anthocyanins could be more potent inhibitors of β‐catenin.…”
Section: Resultsmentioning
confidence: 99%
“…[13] In general, tumor formation occurs due to the abnormal Wnt signaling by nuclear accumulation of β-catenin as a result of glycogen synthetase kinase-3 (GSK-3)β inactivation. [14] According to molecular docking results, we proposed that four anthocyanins could be more potent inhibitors of β-catenin. Therefore, we speculated that AMA had a certain inhibition on Wnt/βcatenin signaling pathway and then carried out cell assay to study and verify it.…”
Section: Parameter-based Docking Analysis Of Four Major Anthocyanins mentioning
confidence: 99%
“…However, this is the predicted docking pocket, more experiments, such as the mutation of crucial residues will reveal the accurate residues responsible for the activity of EgGps and for protein-ligand interaction. Based on these data, together with molecular dynamics simulations which can evaluate the molecular flexibility of ligands and receptors, more accurate docking and virtual screening methods (Tao et al, 2019;Wang et al, 2020), the promising hits targets EgGps will be found and benefit the development of anti-echinococcal compounds. The interactions of these compounds with Gps were proven in vitro by determining the activity of Gps in PSC homogenates.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, molecular docking simulations (MDS) show promise in direct elucidation of the specific binding sides being involved in such interactions and the affinity between the two active constituents [101]. In general, molecular docking will examine a range of hypothetical protein structures to decide on the most stable configuration on energetic grounds taking into consideration the non-covalent interactions that stabilise the complex [102].…”
Section: Pinpointing the Biding Sies With Molecular Docking Simulationsmentioning
confidence: 99%
“…The types of software include, AutoDock, DOCK, GOLD, ICM, Glide, Surflex, Affinity, LigandFit, Discovery Studio and many others are well-reviewed in the literature [102,104,105]. The most recent docking programs in the last 5 years are CABS-dock, FlexAID, GalaxyPepDock, LightDock and MOLS 2.0 [106][107][108][109][110].…”
Section: Pinpointing the Biding Sies With Molecular Docking Simulationsmentioning
confidence: 99%